2018
DOI: 10.1016/j.jconrel.2018.02.041
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular self assembly of nanodrill-like structures for intracellular delivery

Abstract: Despite recent advances in the supramolecular assembly of cell-penetrating peptide (CPP) nanostructures, the tuning of size, shape, morphology and packaging of drugs in these materials still remain unexplored. Herein, through sequential ligation of peptide building blocks, we create cell-penetrating self-assembling peptide nanomaterials (CSPNs) with the capability to translocate inside cells. We devised a triblock array of Tat [HIV-1 derived transactivator of transcription] based CPPs, conjugated to up to four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 72 publications
(58 reference statements)
0
18
0
Order By: Relevance
“…On self-assembling, hydrophilic residues of amino acids are located toward the exterior water phase while hydrophobic residues are buried in the core, contributing to the unique structures of β sheeted materials that are effective for small molecule or gene delivery applications (Figure 7A) 108. The first β sheet nanomaterial, RADA 16, has been utilized for drug delivery 109,110, regenerative medicine (neural stem cell differentiation) 111, in vivo brain damage repair and bone regeneration 112,113. The SAPs that form the nanostructures with a high aspect ratio, like ribbons, fibrils, and fibers, with varied numbers of β sheets in the final structures.…”
Section: Supramolecular Self-assembly Of Peptidesmentioning
confidence: 99%
See 2 more Smart Citations
“…On self-assembling, hydrophilic residues of amino acids are located toward the exterior water phase while hydrophobic residues are buried in the core, contributing to the unique structures of β sheeted materials that are effective for small molecule or gene delivery applications (Figure 7A) 108. The first β sheet nanomaterial, RADA 16, has been utilized for drug delivery 109,110, regenerative medicine (neural stem cell differentiation) 111, in vivo brain damage repair and bone regeneration 112,113. The SAPs that form the nanostructures with a high aspect ratio, like ribbons, fibrils, and fibers, with varied numbers of β sheets in the final structures.…”
Section: Supramolecular Self-assembly Of Peptidesmentioning
confidence: 99%
“…Short aromatic peptides such as FF, FY, Fmoc-FF, and Nap-FF have shown that the incorporation of those peptide can cause self-assembly of peptides via strong aromatic π-π stacking 145. Recently, Ashwanikumar et al reported that the structures of self-assembled peptide-based nanomaterials can be manipulated from a random coil, a distorted α-helix, a β-sheet, or to a pure α-helix by changing the number of phenylalanine in the sequence 109. The twisted drill-like nanostructures showed the highest internalization as compared to the other regular cylindrical counterparts in vitro and in vivo .…”
Section: Supramolecular Self-assembly Of Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…A new example has employed Tat peptides conjugating with a RADA sequence to obtain supramolecularly assembled nanodrills for the intracellular delivery of hydrophobic therapeutics (Fig. 2 ) [ 73 ]. In this design, the cell-penetrating peptide (CPP) Tat derived from HIV1 donates a hydrophobic sequence, providing a high capacity for biological membrane penetration [ 74 ]; a RADA sequence modified with various phenylalanine (Phe, F) residues provides a supramolecular complex driving force with a β-sheet formation and π–π stacking.…”
Section: Supramolecular Drug Carriersmentioning
confidence: 99%
“…Inspired by recent advances in peptide self-assembly and cell penetrating macromolecules, in particular self-assembled cell penetrating peptides, [25][26][27][28][29][30][31] we have developed a new class of peptide assemblies with intrinsic cell penetrating activity, termed supramolecular cell penetrating nanobers (SCPNs). [32][33][34][35] SCPNs are generated through the self-assembly of de novo designed cationic multidomain peptides (MDPs) with a general sequence of K x (QW) 6 (K: lysine, Q: glutamine; W: tryptophan).…”
Section: Introductionmentioning
confidence: 99%